2005
DOI: 10.4269/ajtmh.2005.73.510
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Iron Superoxide Dismutase Excreted by Trypanosoma Cruzi in the Diagnosis of Chagas Disease: Seroprevalence in Rural Zones of the State of Queretaro, Mexico

Abstract: Four iron superoxide dismutase (SODI, SODII, SODIII, and SODIV) activities with pI values of 6.9, 6.8, 5.25, and 3.8, respectively, were isolated from epimastigote forms of the Maracay strain of Trypanosoma cruzi cultivated at 28 degrees C in Grace's medium supplemented with 10% heat-inactivated fetal bovine serum. The activity of SODe (pI 3.8), which coincides with that of SODIV, was detected in Grace's medium without serum in which T. cruzi epimastigotes were cultivated for 24 hours at 28 degrees C. SODe, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 25 publications
2
32
1
1
Order By: Relevance
“…Each peak was further purified separately by filtration chromatography, giving rise to a total of four SOD activities [called SOD I, II, III and IV, according to the nomenclature used by Villagrán et al (2005)]. This is consistent with the results revealed by IEF since the P85 fraction showed four bands of SOD activity.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Each peak was further purified separately by filtration chromatography, giving rise to a total of four SOD activities [called SOD I, II, III and IV, according to the nomenclature used by Villagrán et al (2005)]. This is consistent with the results revealed by IEF since the P85 fraction showed four bands of SOD activity.…”
Section: Discussionsupporting
confidence: 71%
“…The SOD activity identification is possible only under the native conditions of the protein; thus, we have detected four different isoenzymes by IEF 3-9 and native electrophoresis. According to Villagrán et al (2005), we have found different pI: 6.9, 6.8, 5.2 and 3.8 for SOD I, SOD II, SOD III and SOD IV, respectively. The pIs ob- Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extracellular SODs (EcCu/ZnSODs) have been evidenced in invertebrates, in several species of nematodes, such as, Brugia pahangi (Tang et al 1994), Onchocerca volvulus (James et al 1994), and Caenorhabditis elegans (Fujii et al 1998) and the crustacean Callinectes sapidus (Brouwer et al 2003). Recently, Villagrán et al (2005) have shown the presence of a iron SODe in T. cruzi. Also, in mammals, several researchers have studied extracellular SOD (EC-SOD), which is the major extracellular antioxidant enzyme and plays a critical role in the pathogenesis of a variety of pulmonary, neurological, and cardiovascular diseases (Suliman et al 2001, Fukai et al 2002.…”
mentioning
confidence: 99%